Rethinking Figurative Language in Autism: What Evidence Can We Use for Interventions? - Vulchanova, Mila; Vulchanov, Valentin (Frontiers in Communication, 2022)
Problems with the processing and understanding of figurative language have been systematically observed in individuals on the autism spectrum despite preserved structural language skills. In this qualitative review we discuss theoretical considerations of relevance for figurative language processing in neurotypical individuals and individuals with autism across the life-span. We address the factors which influence figurative language processing and their role in the processing of different types of figurative language, with a focus on idioms and metaphors. We address critically the evidence from research, including findings in our own research and recent systematic reviews and the extent to which they offer a reliable picture of potential deficits in figurative language processing in autism and their possible sources. This evidence is discussed from the point of view of insights it offers for interventions targeting non-literal language skills in children and adults with autism.